Quality Analysis of Accrual-Based Accounting Implementation in Local Governments (Comparative of Padang Pariaman Regency and Solok City) - Nur Rahmanely; Suhairi (Pandawan, 2023)
The purposes of this research are to see the result of quality assessment in accrual-based accounting implemented in Regional Apparatus Organization (OPD) in Padang Pariaman Regency and Solok City Government and to see whether there is the different quality of accrual accounting implemented between the two regions. Assessment of the quality of the implemented accrual-based accounting comes from the time of recognition of the transaction. The rate of accounting quality based on accrual is taken through five kinds of accrual transactions, namely asset-to-expense conversion transactions, unpaid expense accrual transactions, unpaid asset accrual transactions, uncollected income transactions, and liabilities-to-income conversion transactions. The method used in this research is a quantitative approach in the form of comparison. The data used in this study is the questionnaire forms of respondents as primary data. The respondents chosen are financial statement maker apparatus. The results showed that there were significant differences in the quality of accrual-based accounting implementation to OPD in Padang Pariaman Regency and Solok City.